Disputed Translations from The Life and Struggles of Our Mother Walatta Petros (2015) Reconsidered: Some Notes on Gǝʿǝz Philology - Michael Kleiner (Aethiopica)
The present article was prompted by Yirga Gelaw Woldeyes’s ‘Colonial Rewriting of African History: Misinterpretations and Distortions in Belcher and Kleiner’s Life and Struggles of Walatta Petros’ as published in a special issue of the Journal of Afroasiatic Languages, History and Culture in the fall of 2020. Yirga’s text of more than eighty pages is a wide-ranging and often acrimonious critique of Wendy Laura Belcher’s and my scholarship in our 2015 annotated translation of the Gädlä Wälättä Ṗeṭros. This reply does not attempt to address all the philological and non-philological issues Yirga raises. Rather, it focuses on refuting Yirga’s allegations of sexualizing mistranslations on our part. As these alleged mistranslations form the virtually exclusive basis for Yirga’s more far-reaching accusations against our scholarship, refuting them also collapses his broader case.